On the Time and Temperature Dependent Behaviour of Laminated Amorphous Polymers Subjected to Low-Velocity Impact - Rühl, Andreas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer Vieweg, 2017)
The thesis investigates a polymeric laminate consisting of poly(methyl methacrylate) (PMMA) and thermoplastic polyurethane (TPU) experimentally and numerically with regard to its impact behaviour and applicability. After a basic characterization of the monolithic materials, PMMA-TPU-PMMA laminates were subjected to impact loadings at velocities up to 5 m/s using threepoint bending and dart impact tests. Based on the experimental basis, different material models for the Finite Element simulation are presented, which are able to capture the time and temperature dependent behaviour of the laminate. Final validation experiments, consisting of head-dummy impacts at 10 m/s on automotive side windows, were conducted for PMMA and the laminate in order to investigate their applicability as glass substitution products. The Content Introduction · Fundamentals · Experimental Investigation · Material Modelling of PMMA · Material Modelling of TPU · Simulation of PMMA-TPU Laminate · Component Tests and Validation · Summary and Outlook The Author Dr.-Ing. Andreas Rühl studied Mechanical Engineering at the Technische Hochschule Mittelhessen in Gießen. Since 2011 he is employed at the Institute of Mechanics and Materials as a research associate in the working group of Prof. Dr.-Ing. habil. Stefan Kolling. During this time he completed his doctorate (Dr.-Ing.) in a cooperative graduation with the Technical University Darmstadt in the working group of Prof. Dr.-Ing. Jens Schneider. His research interests are in the area of thermomechanical characterization and modelling of polymeric materials. .
Introduction -- Fundamentals -- Experimental Investigation -- Material Modelling of PMMA -- Material Modelling of TPU -- Simulation of PMMA-TPU Laminate -- Component Tests and Validation -- Summary and Outlook.
Keywords: Mechanics, Applied; Solids; Materials -- Analysis; Materials; Solid Mechanics; Characterization and Analytical Technique; Materials Engineering